The Effectivity of Microsoft Word Layout for quadriplegic Through a technology of webcam used as a mouse - Jessica Kristanti Utomo; Erandaru -; Jacky Cahyadi (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2021)
A quadriplegic is a person who is not able to do activities like normal people due to disablement in their body. During this vast digital age, a technological invention that can help people with quadriplegic is the web camera that is used as a mouse— called a camera mouse— for the computer. Which can then be implemented with Microsoft word software so it can help to access a computer or laptop. Before being used with the camera mouse, Microsoft word itself requires a special mode, namely physical distancing mode. This mode will later be a plugin that can be activated in Microsoft word. The existing Microsoft word layout has not been able to accommodate the use of the camera mouse without errors. The current Microsoft word software is not able to stand alone incorporating a camera mouse because the layout does not accommodate the works of the camera mouse. Therefore, a plugin is needed to support the software, named an accessibility mode.